Intrapelvic Wilms' tumor simulating xanthogranulomatous pyelonephritis - Groeneveld, D; Robben, S G; Meradji, M; Nijman, J M (Pediatric radiology, 1995)
A 2-year-old boy presented with an atypical renal mass with extension into the pyelocalyceal system and distal ureter which was diagnosed initially as xanthogranulomatous pyelonephritis (XGP). The final diagnosis was intrapelvic Wilms tumor extending into the ureter. In the literature, only three patients have been described with Wilms tumor extending into the ureter, none of whom had a continuous extension into the distal ureter.